Structural, dielectric, ferroelectric and tuning properties of Pb-free ferroelectric Ba0.9Sr0.1Ti1-xSnxO3. Issue 17 (1st December 2020) - Zaitouni, H.; Hajji, L.; Mezzane, D.; Choukri, E.; Gagou, Y.; Hoummada, K.; Charai, A.; Alimoussa, A.; Rožič, B.; El Marssi, M.; Kutnjak, Z.
Abstract: A series of Pb-free ferroelectric materials Ba0.9 Sr0.1 Ti1-x Snx O3 (BSTS-x) with 0 ≤ x ≤ 0.15 was successfully prepared via solid-state reaction method. The effect of Sn substitution on the crystal structure, microstructure, dielectric behavior, ferroelectric and tunable features of BSTS-x ceramics were systematically investigated. Room temperature (RT) x-ray diffraction (XRD) analysis using the Rietveld refinement method reveals that all the synthesized BSTS-x ceramics were well crystallized into single perovskite structure. The results show a tetragonal phase for 0.00 ≤ x ≤ 0.02, which evolves to orthorhombic and tetragonal coexisting phases for 0.05 ≤ x ≤ 0.07. The composition x = 0.10 showed a mixture of tetragonal, orthorhombic and rhombohedral phases at RT, while a single cubic phase is observed for x = 0.15. The crystal phases determined by XRD were confirmed by Raman spectroscopy. Enhanced dielectric permittivity with a maximum value of ε ' 35000 is observed for x = 0.10 at RT. The ferroelectric behavior of BSTS-x ceramics was investigated through polarization hysteresis loops and tunability measurements. High tunability of 63% at RT and under the low DC-applied electric field of 1.40 kV/cm is achieved for x = 0.10.